REALITAS SOSIAL DALAM NOVEL PINTU KARYA FIRA BASUKI - Nofrianti, Nofrianti; Bahardur, Iswadi; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2013)
This study uses sociological approach to literature. Analyzing from sociology view the literature that talks about social issues contained in the literature. The purpose of this study is to describe the social reality in the novel Pintu works Fira Basuki.This research is qualitative research. The method used in this research is descriptive. The data in this study in the form of word, sentences and dialogue related to social reality. Based on the analysis of the study, we found social reality of relationships in the community with social reality in the novel Pintu works Fira Basuki i.e : Java and European public confidence, spiritual beliefs, traditions, and way of life. From this analysis it can be concluded. First, novel Pintu that is full of Indonesian contemporary social problems. Second, novel Pintu Fira Basuki work raised a number of social issues that occur in the middle of the traditional and the modern Indonesian society. Third, there is a social reality in the novel Pintu related to the problems of Java and European public trust , faith of theÂ communities, traditions, and way of life. Fourth, the novel works Fira Basuki Pintu has the benefit that can be used for teaching elements of literary readers.